The Delayed Acceptance of Female Research in Economics - Stephan B. Bruns; Anthony Doucouliagos; Chris Doucouliagos; Johannes König; Tom D. Stanley; Katarina Zigova (Institute of Labor Economics (IZA), 2025)
We investigate gender differences in the time taken to accept empirical articles. On average, female-authored economics articles take notably longer to accept. Acceptance delay is nine weeks longer when solo-authored and five weeks longer for all female teams. This gender gap cannot be attributed to differences in author affiliation, research productivity, research quality and novelty. Female-authored articles are of higher quality, as measured by citations, reflecting higher research thresholds for female-authored work. The gender composition of editorial boards does not affect acceptance time for female authors. Nevertheless, this gender gap narrows as female representation in an area of research deepens.
Keywords: J16; 330; social norms; economics journals; acceptance time; gender